Restorative Justice Arrangements in the Indonesian Criminal Justice System: A Contribution of Thoughts - Abdul Wahid (Rechtsidee, 2021)
The criminal justice system has an orientation to involve various components to prevent the occurrence of criminal acts. In the practice of criminal law, the idea of ​​restorative justice has emerged in the practice of law in Indonesia. This study aims to initiate the regulation of restorative justice in the Criminal Procedure Code as part of the criminal justice system's development. This research is normative legal research oriented to the study and analysis of positive law. This study examines the legal issue, namely the legal vacuum in the regulation of restorative justice in the Criminal Procedure Code. The study results confirm that restorative justice is part of the criminal justice system, especially in the aspect of the criminal justice system process, which effectively and efficiently strengthens the orientation of the legal process effectively and efficiently in criminal law enforcement. In this context, restorative justice is part of the development of legal theory and practice and an effort to revive the value of local wisdom in Indonesian criminal law. The Ius constituendum or future arrangements related to restorative justice in the Criminal Procedure Code need to be carried out so that the Criminal Procedure Code can guide the implementation of formal law in Indonesia that has Indonesian aspirations, especially with the application of restorative justice in practice as well as the pouring of restorative justice in the Criminal Procedure Code which is essential to ensure legal certainty as well as provide a dimension of harmony for restorative justice arrangements